The Influence of Squat Jump and Knee Tuck Jump Exercises on Leg Muscle Explosive Power in Male Volleyball Extracurricular Students at SMA Negeri 3 Pati - Ika Latvia Widya Pangestika; Agung Wahyudi (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of squat jump and knee tuck jump exercises on leg muscle explosive power in male volleyball extracurricular students at SMA Negeri 3 Pati. The research employed a quantitative method with a pre-test and post-test experimental design. The sample consisted of 14 male students selected using total sampling technique. The subjects were divided into two groups: the experimental group I received squat jump training, while the experimental group II received knee tuck jump training. Each group underwent 14 training sessions. The instrument used to measure leg muscle explosive power was the vertical jump test. Prior to data analysis, normality and homogeneity tests were conducted, followed by hypothesis testing using the paired sample t-test with a significance level of α = 0.05. The results showed that the average pre-test and post-test scores in experimental group I were 236.57 and 286.00, respectively, while in experimental group II they were 244.71 and 289.14, respectively. The t-test results indicated that the calculated t-value of 0.733 was lower than the t-table value of 2.179 with a significance value (p) of 0.478 (p > 0.05), thus the null hypothesis (H₀) was accepted. Therefore, it can be concluded that there is no significant difference in the improvement of vertical jump performance between students who underwent squat jump training and those who underwent knee tuck jump training.